Efficacy of a dyadic intervention to improve communication between patients with cancer and their caregivers: A randomized pilot trial. Issue 3 (March 2021) - Tiete, Julien; Delvaux, Nicole; Liénard, Aurore; Razavi, Darius
Highlights: Cancer-related dyadic communication is a key component of adaptation to illness. This pilot study tested feasibility, acceptability and efficacy of a dyadic intervention. The test intervention tended to equally promote patients' and caregivers' disclosure and requests for support. The test intervention was acceptable and feasible. Results showed preliminary evidence of the test intervention efficacy. Abstract: Objective: Cancer-related communication is critical for patients' and caregivers' adaptation to illness. This randomized pilot study was conducted to test the feasibility, acceptability, and efficacy of a specific dyadic intervention to improve communication. Methods: A four weekly-session intervention was developed to reinforce cancer-related patient-caregiver communication. Patients receiving treatment for any diagnosed cancer, and their caregivers, were recruited from two oncology clinics in Belgium. Sixty-four patient-caregiver dyads were assigned randomly to intervention and waitlist groups. Cancer-related dyadic communication, dyadic coping and emotional distress were assessed at baseline and post-intervention. Results: The intervention attrition rate was 6 %. Linear mixed models were performed on 60 dyads. Significant two-way group × time interaction indicated improvement in participants' cancer-related dyadic communication frequency (β = −1.30; SE = 0.31; p  =  .004), self-efficacy (β = −10.03; SE = 3.90; p  =  .011) and dyadic coping (β = −5.93; SE = 2.73; p  =  .046) after the intervention. Conclusion: These results indicate that the brief dyadic communication intervention is feasible and acceptable, and show preliminary evidence of efficacy. Practice implications: Encouraging patients and caregivers to discuss personal cancer-related concerns may improve their ability to cope with the illness together.